2014
DOI: 10.1159/000368080
|View full text |Cite
|
Sign up to set email alerts
|

Benidipine Suppresses in situ Proliferation of Leukocytes and Slows the Progression of Renal Fibrosis in Rat Kidneys with Advanced Chronic Renal Failure

Abstract: Background/Aims: Leukocytes, such as lymphocytes and macrophages, predominantly express delayed rectifier K+ channels (Kv1.3) in their plasma membranes. In our previous study, the overexpression of these channels in leukocytes was strongly associated with their proliferation in kidneys and the progression of renal fibrosis in advanced-stage chronic renal failure (CRF). Since benidipine, a long-acting 1,4-dihydropyridine Ca2+ channel blocker, is also highly potent as a Kv1.3 channel inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 34 publications
2
33
1
Order By: Relevance
“…Additionally, the persistent effect of benidipine in decreasing the channel currents suggested its longer duration of action in thymocytes, as previously demonstrated in cardiomyocytes [153] and isolated coronary arteries [154]. In our recent study using a rat model of advanced CRF [98], benidipine, by suppressing the in situ proliferation of kidney lymphocytes, actually repressed their cytokine production, and thus ameliorated the progression of renal fibrosis. In respiratory diseases, such as asthma and lung carcinoma, verapamil, which also totally and almost irreversibly inhibited the Kv1.3-channel currents in our most recent patch-clamp study [59] ( Table 2), has actually been shown to be useful in the prophylaxis and treatment of the diseases [155][156][157][158].…”
Section: Calcium Channel Blockers Statins and Nsaids As Potent Kv1supporting
confidence: 66%
See 1 more Smart Citation
“…Additionally, the persistent effect of benidipine in decreasing the channel currents suggested its longer duration of action in thymocytes, as previously demonstrated in cardiomyocytes [153] and isolated coronary arteries [154]. In our recent study using a rat model of advanced CRF [98], benidipine, by suppressing the in situ proliferation of kidney lymphocytes, actually repressed their cytokine production, and thus ameliorated the progression of renal fibrosis. In respiratory diseases, such as asthma and lung carcinoma, verapamil, which also totally and almost irreversibly inhibited the Kv1.3-channel currents in our most recent patch-clamp study [59] ( Table 2), has actually been shown to be useful in the prophylaxis and treatment of the diseases [155][156][157][158].…”
Section: Calcium Channel Blockers Statins and Nsaids As Potent Kv1supporting
confidence: 66%
“…As we recently demonstrated in kidneys with chronic inflammation [61,98], the activity of T lymphocytes and their in situ proliferation within the peripheral organs are largely dependent on the activity of the Kv1.3-channels and their expression level. Therefore, in this context, it is most likely that the channels are also over-activated or overexpressed in T lymphocytes in these acute or chronic respiratory diseases.…”
Section: In Respiratory Diseasesmentioning
confidence: 80%
“…Rats with 5/6 nephrectomy and 8‐week recovery periods were used as the model of CRF in the present study. Subtotal nephrectomy was performed in male Sprague–Dawley rats weighing 150–180 g (Japan SLC, Shizuoka, Japan) as described in our previous studies . Briefly, the upper third and lower third of the right kidney were ligated to induce infarction.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in our series of patch-clamp studies, commonly used drugs, such as calcium channel blockers (CCBs) [25, 27], macrolide antibiotics [24], HMG-CoA reductase inhibitors (statins) [26] and nonsteroidal anti-inflammatory drugs (NSAIDs) [23], also effectively inhibited the Kv1.3-channel currents in thymus-derived murine lymphocytes. Of note, benidipine, one of the dihydropyridine-type CCBs, which most strongly and persistently inhibited the channel currents [25], actually suppressed the proliferation of kidney lymphocytes, and thus ameliorated the progression of renal fibrosis [47]. In this regard, in addition to using the previously developed selective blockers for the channels [4850], the use of CCBs, macrolide antibiotics or statins could also potentially be useful in the treatment of COPD (Fig.…”
Section: Therapeutic Implications Of Targeting Kv13-channels In the mentioning
confidence: 99%